HUBUNGAN TINGKAT PENDIDIKAN ORANG TUA DENGAN MOTIVASI MELANJUTKAN KEPERGURUAN TINGGI PADA KELAS XII IPS - Sari, Della; Asriati, Nuraini; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this study was to determine the relationship between the level of education of parents with the motivation to continue their tertiary education in class XII IPS at SMAN 2 Sungai Raya. The population is 99 students of class XII IPS. The method used is descriptive method. Data collection uses indirect communication techniques and documentary study techniques. The data analysis technique uses chi-square test calculations and contingency coefficient. The results of the study showed that (1) the level of education category possessed by parents of students was mostly upper secondary education with a percentage of 44.4%, (2) The motivation of students to continue their tertiary education is that they have a high level of motivation to continue their tertiary education with a percentage of 38.4% in the very high category, (3)  count >   table = 22,924> 21,026 means that Ho is rejected. This shows that there is a relationship between the level of education of parents and the motivation of students to pursue higher education in class XII IPS at SMAN 2 Sungai Raya. The relationship between the level of parental education and the motivation to continue tertiary education can be said to be moderate, The relationship between the level of parental education and the motivation to continue tertiary education can be said to be moderate. Keywords: Parents' Education Level, Parent's Role, Motivation to Continue College Education.